Effects of the incorporation of ε-aminocaproic acid/chitosan particles to fibrin on cementoblast differentiation and cementum regeneration. (1st October 2017) - Park, Chan Ho; Oh, Joung-Hwan; Jung, Hong-Moon; Choi, Yoonnyoung; Rahman, Saeed Ur; Kim, Sungtae; Kim, Tae-Il; Shin, Hong-In; Lee, Yun-Sil; Yu, Frank H.; Baek, Jeong-Hwa; Ryoo, Hyun-Mo; et al.
Graphical abstract: Abstract: Cementum formation on the exposed tooth-root surface is a critical process in periodontal regeneration. Although various therapeutic approaches have been developed, regeneration of integrated and functional periodontal complexes is still wanting. Here, we found that the OCCM30 cementoblasts cultured on fibrin matrix express substantial levels of matrix proteinases, leading to the degradation of fibrin and the apoptosis of OCCM30 cells, which was reversed upon treatment with a proteinase inhibitor, ε-aminocaproic acid (ACA). Based on these findings, ACA-releasing chitosan particles (ACP) were fabricated and ACP-incorporated fibrin (fibrin-ACP) promoted the differentiation of cementoblasts in vitro, as confirmed by bio-mineralization and expressions of molecules associated with mineralization. In a periodontal defect model of beagle dogs, fibrin-ACP resulted in substantial cementum formation on the exposed root dentin in vivo, compared to fibrin-only and enamel matrix derivative (EMD) which is used clinically for periodontal regeneration. Remarkably, the fibrin-ACP developed structural integrations of the cementum-periodontal ligament-bone complex by the Sharpey's fiber insertion. In addition, fibrin-ACP promoted alveolar bone regeneration through increased bone volume of tooth roof-of-furcation defects and root coverage. Therefore, fibrin-ACP can promote cementogenesis and osteogenesis by controlling biodegradability of fibrin, implicating the feasibility of its therapeutic use to improve periodontal regeneration. Statement of Significance: Cementum, the mineralized layer on root dentin surfaces, functions to anchor fibrous connective tissues on tooth-root surfaces with the collagenous Sharpey's fibers integration, of which are essential for periodontal functioning restoration in the complex. Through the cementum-responsible fiber insertions on tooth-root surfaces, PDLs transmit various mechanical responses to periodontal complexes against masticatory/occlusal stimulations to support teeth. In this study, periodontal tissue regeneration was enhanced by use of modified fibrin biomaterial which significantly promoted cementogenesis within the periodontal complex with structural integration by collagenous Sharpey's fiber insertions in vivo by controlling fibrin degradation and consequent cementoblast apoptosis. Furthermore, the modified fibrin could improve repair and regeneration of tooth roof-of-furcation defects, which has spatial curvatures and geometrical difficulties and hardly regenerates periodontal tissues.